Adenocarcinoma of the Right Colon in a Patient with Bloom Syndrome. (15th August 2016) - Martinez, Carlos Augusto Real; Pinheiro, Lilian Vital; Rossi, Debora Helena; Camargo, Michel Gardere; Ayrizono, Maria de Lourdes Setsuko; Leal, Raquel Franco; Coy, Cláudio Saddy Rodrigues
Abstract : Introduction . Bloom syndrome (BS) is an inherited disorder due to mutation in BLM gene. The diagnosis of BS should be considered in patients with growth retardation of prenatal onset, a photosensitive rash in a butterfly distribution over the cheeks, and an increased risk of cancer at an early age. Clinical manifestations also include short stature, dolichocephaly, prominent ears, micrognathia, malar hypoplasia and a high-pitched voice, immunodeficiency, type II diabetes, and hypogonadism associated with male infertility and female subfertility. The aim of this report is to describe case of patient with BS who developed adenocarcinoma of the cecum, successfully treated by right colectomy. Case Report . A 40-year-old man underwent colonoscopy to investigate the cause of his diarrhea, weight loss, and anemia. The patient knew that he was a carrier of BS diagnosed at young age. The colonoscopy showed an expansive and vegetating mass with 5.5 cm in diameter, located within the ascending colon. Histopathological analysis of tissue fragments collected during colonoscopy confirmed the presence of tubular adenocarcinoma, and he was referred for an oncological right colectomy. The procedure was performed without complications, and the patient was discharged on the fifth postoperative day. Histopathological examination of the surgical specimen confirmed the presence of a grade II tubular adenocarcinoma (stage IIA). The patient is currently well five years after surgery, without clinical or endoscopic signs of relapse in a multidisciplinary approach for the monitoring of comorbidities related to BS. Conclusion . Despite the development of colorectal cancer to be, a possibility rarely described the present case shows the need for early screening for colorectal cancer in all patients affected by BS.